2003
DOI: 10.1128/aem.69.9.5707-5710.2003
|View full text |Cite
|
Sign up to set email alerts
|

Survival of F-Specific RNA Coliphage, Feline Calicivirus, andEscherichia coliin Water: a Comparative Study

Abstract: The relationship between the survival of enteric viral pathogens and their indicators (coliform bacteria and coliphages) is not well understood. We compared the survival rates of feline calicivirus (FCV), Escherichia coli, and a male-specific RNA coliphage MS2 at 4, 25, and 37°C for up to 28 days in dechlorinated water. The survival rates of E. coli and FCV, a surrogate of noroviruses (NV), had a high degree of correlation at 4 and 25°C, while MS2 phage survived significantly longer (P < 0.05) at these two tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 39 publications
6
62
0
Order By: Relevance
“…This acceleration in the inactivation kinetics of F-specific bacteriophages with increasing temperatures is also observed in experiments with laboratory-grown bacteriophages. Thus, McLaughlin and Rose described very high decay rates for MS2, an F-specific bacteriophage, in seawater at 30˝C [110], and Allwood et al revealed that the decay rate of MS2 at 37˝C is even greater than that of E. coli [111]. All these results suggest that the persistence of F-specific RNA phages might be rated as low in waters with temperatures greater than 25˝C.…”
Section: Persistence In Water Environments and Resistance To Treatmentmentioning
confidence: 62%
“…This acceleration in the inactivation kinetics of F-specific bacteriophages with increasing temperatures is also observed in experiments with laboratory-grown bacteriophages. Thus, McLaughlin and Rose described very high decay rates for MS2, an F-specific bacteriophage, in seawater at 30˝C [110], and Allwood et al revealed that the decay rate of MS2 at 37˝C is even greater than that of E. coli [111]. All these results suggest that the persistence of F-specific RNA phages might be rated as low in waters with temperatures greater than 25˝C.…”
Section: Persistence In Water Environments and Resistance To Treatmentmentioning
confidence: 62%
“…Allwood et al (2003) analysed inoculated potable water with Feline Calicivirus (FCV) at 4, 25 and 378C, during 28 days. They found that an increment in temperature diminished the time required for 90% viral reduction at 7.3, 5.2 and 2 days, respectively.…”
Section: Results and Discussion Presence Of Hav And Nv In Mrwsmentioning
confidence: 99%
“…However, conclusive data remarks negative correlation between Enterococci and viral pathogens (APHA 1999; Griffin et al 1999;Jiang et al 2001;Harwood et al 2005;Moce et al 2005;Vantarakis et al 2005). Viruses are known to persist for a longer time in MRWs (Allwood et al 2003).…”
Section: Information About the Presence Of Enteric Viruses Inmentioning
confidence: 99%
“…Enteric viruses are one of the most important causative agents of waterborne gastroenteritis because of their high infectivity (13,43), persistence in water (1,2), and tolerance to wastewater treatment (9,33) and chlorination (44). Therefore, monitoring viruses in the environment is important for protecting public health (48).…”
mentioning
confidence: 99%